2020
DOI: 10.3390/nu12113587
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fermented Red Clover Extract on Skeletal Muscle in Early Postmenopausal Women: A Double-Blinded Cross-Over Study

Abstract: Objective: To investigate effects of supplementation with a fermented red clover (RC) extract on signaling proteins related to muscle protein synthesis and breakdown at rest and in response to a resistance exercise bout. Methods: Ten postmenopausal women completed a double-blinded cross-over trial with two different intervention periods performed in random order: (A) RC extract twice daily for 14 days, and (B) placebo drink twice daily for 14 days. The intervention periods were separated by a two-week washout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 60 publications
(99 reference statements)
1
6
0
Order By: Relevance
“…The findings from this study have unearthed novel evidence regarding the cardiovascular benefits of RC, which support the known therapeutic potential of RC in relieving menopausal symptoms (66), promoting bone health (33), and minimizing skeletal muscle breakdown (36) in post-menopausal women. Future investigations are required to elucidate the optimal dosing regime and mechanisms of action, together with reporting of potential side effects.…”
Section: Future Directionssupporting
confidence: 61%
See 1 more Smart Citation
“…The findings from this study have unearthed novel evidence regarding the cardiovascular benefits of RC, which support the known therapeutic potential of RC in relieving menopausal symptoms (66), promoting bone health (33), and minimizing skeletal muscle breakdown (36) in post-menopausal women. Future investigations are required to elucidate the optimal dosing regime and mechanisms of action, together with reporting of potential side effects.…”
Section: Future Directionssupporting
confidence: 61%
“…In recent years, advances in food science and nutraceutical biochemistry have significantly improved the bioavailability, and therefore, the therapeutic potential of red clover isoflavones via the fermentation process, which converts isoflavone glycosides to aglycones ( 33 ). Therefore, fermented red clover extract (RC) may be a safe, easily accessible, and highly efficacious therapeutic intervention to promote cardiovascular and metabolic health as well as bone health ( 33 ) and the maintenance of muscle mass and function ( 36 ) in post-menopausal women. However, to date, no study has evaluated the cardiovascular benefits in a cohort of post-menopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…Endurance athletes in particular are more likely to develop gastrointestinal diseases (20). Supplementation of isoflavones through a fermented red clover extract reduces markers of protein degradation (21), increases lean body mass and muscle mass in postmenopausal women (22).…”
Section: Introductionmentioning
confidence: 99%
“…As one study found in legumes, red clover isoflavone through oestrogen receptor (ER) binding and activation of ER-dependent gene transcription, which has a relatively high binding affinity for the ERα and ERβ, isoflavones demonstrate up to ~1600 times lower affinity for ERα. 45 This may explain the significant effect of isoflavones.…”
Section: Discussionmentioning
confidence: 99%